2020
DOI: 10.1163/22142312-12340119
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Telegram: Iranian Users and ‘Produsaging’ Discourses in Iran’s 2017 Presidential Election

Abstract: This paper investigates the most-viewed posts in Persian Telegram channels during the period surrounding Iran’s 2017 presidential election. Telegram has become the most popular social medium in Iran, and its channels have played a significant role in recent social and political events. Based on the produsage theory and user-generated content concept, this research identifies the popular content and produsagers on Persian Telegram channels. Moreover, this paper evaluates the potential of these most-viewed posts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…En un contexto digital volátil, con la aparición y desaparición de medios sociales cada pocos años, y la consecuente adaptación continua a la que están obligadas las instituciones (Gómez-Calderon y Paniagua-Rojano, 2014), consideramos necesario abordar el estudio de Telegram, una herramienta de comunicación digital de incipiente penetración en el entorno hispanohablante y poco investigada hasta la fecha (Kermani, 2020).…”
Section: La Comunicación Digital Universitariaunclassified
“…En un contexto digital volátil, con la aparición y desaparición de medios sociales cada pocos años, y la consecuente adaptación continua a la que están obligadas las instituciones (Gómez-Calderon y Paniagua-Rojano, 2014), consideramos necesario abordar el estudio de Telegram, una herramienta de comunicación digital de incipiente penetración en el entorno hispanohablante y poco investigada hasta la fecha (Kermani, 2020).…”
Section: La Comunicación Digital Universitariaunclassified
“…Interestingly, since 2013 most of Telegram’s worldwide visits have come from Iran. With 25 million active users in 2016 [ 35 ], the number of Iranian users jumped to 40 million in 2018 [ 45 ] and more than 50 million users by the end of the same year Kermani [ 12 , 36 ] stated that in June 2017, 69.9% of Telegram’s visitors were Iranians. These numbers undoubtedly highlight the vital role the messaging app plays in mass communication inside Iran.…”
Section: Mobile Apps As Portable Alternative News Mediamentioning
confidence: 99%
“…Regarding usage purposes, a 2017 survey found that 70% of Iranians use Telegram for messaging peers and 18% use it for entertainment purposes, with half of those surveyed saying they trusted and, therefore, favoured news coming from Telegram versus traditional state-run Iranian media [ 67 ]. Moreover, in 2017 Telegram had more than 380,000 Persian channels with over two million posts published daily [ 36 , p. 4]. More importantly, Marchant et al [ 45 ] emphasize that much more research needs to be conducted to “effectively map the structure and dynamics of Persian-language Telegram, and additional tools are required to adapt to the specific challenges of Telegram’s … networks, a hybrid between a traditional social media platform and a conventional messaging app” [ 45 , p. 38].…”
Section: Mobile Apps As Portable Alternative News Mediamentioning
confidence: 99%
“…' and social media (e.g. Fahadi 2022;Kermani 2020;Seto 2020, Sharbaugh & Nguyen 2014Tapsell 2014). Throughout, the most common concerns among scholars tended to be 'political' -a term with high frequency (Farooq 2022;Hicks 2017;Hussain & Lee 2021;Schmidt 2018;Sheikh 2021;Yang & Kang 2021), for instance, with regard to questions of citizenship and community (see Schneider 2019) as well as participation and democracy (see Lee 2021).…”
mentioning
confidence: 99%